2014
DOI: 10.1007/s00246-014-0903-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Factor XIII Levels After Open Heart Surgery for Congenital Heart Defects: Do Cyanotic and Acyanotic Patients Differ?

Abstract: Cardiopulmonary bypass (CPB) reduces coagulation factor levels through hemodilution and consumption. Differences in CPB-induced alterations of factor XIII (FXIII) levels in children with cyanotic and acyanotic congenital heart defects (CHDs) are not well characterized. FXIII activity (determined by Berichrom assay), prothrombin index, activated partial thromboplastin time, and fibrinogen were measured before open heart surgery with CPB and 5 days postoperatively for children older than 3 years with acyanotic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Moreover, we demonstrated that V34L could act as a protective inherited predisposition to ischemic diseases, as well as a risk factor predisposing to intracerebral hemorrhage [ 41 ]. Finally we showed that low circulating FXIIIA levels in the first days after AMI are associated with the worst prognosis in a short-term survey [ 2 ], in line with other reports focused on different pathological contexts [ 29 , 42 , 43 ].…”
Section: Introductionsupporting
confidence: 90%
“…Moreover, we demonstrated that V34L could act as a protective inherited predisposition to ischemic diseases, as well as a risk factor predisposing to intracerebral hemorrhage [ 41 ]. Finally we showed that low circulating FXIIIA levels in the first days after AMI are associated with the worst prognosis in a short-term survey [ 2 ], in line with other reports focused on different pathological contexts [ 29 , 42 , 43 ].…”
Section: Introductionsupporting
confidence: 90%
“…A postoperative transient CSVT was diagnosed in one case, but this patient also received rFVIIa, which is a known thrombogenic agent associated with increased mortality after cardiac surgery . Neonates and infants with CHD are generally at increased risk of thromboembolic complications because of a CHD‐associated imbalance between pro‐ and antithrombotic activity, abnormally low blood flow velocities and prothrombotic foreign materials . Hunt et al .…”
Section: Discussionmentioning
confidence: 99%
“…The threshold level to have clinical manifestations is below 3-5% of the normal distribution. Additionally, low FXIII levels, can be caused by impaired synthesis, as can be observed following chemotherapy [8,29] and chronic liver failure [10,30], as well as in recurrent bleeding, inflammation, disseminated intravascular coagulation, burn wounds, sepsis, after open heart surgery, in inflammatory bowel disease [31][32][33][34][35][36], and also, as recently definitively demonstrated, in the acute phases of myocardial infarction [37].…”
Section: Fxiii Deficiency Classical Symptoms and Fxiii Therapymentioning
confidence: 99%